Herpes simplex virus-1 KOS-63 strain is virulent and causes titer-dependent corneal nerve damage and keratitis - Hamid-Reza Moein (Nature Portfolio, 2021)
Abstract To investigate the acute clinical, immunological, and corneal nerve changes following corneal HSV-1 KOS-63 strain inoculation. Corneas of C57BL/6 mice were inoculated with either low dose (Ld) or high dose (Hd) HSV-1 KOS-63 or culture medium. Clinical evaluation was conducted up to 7 days post inoculation (dpi). Viral titers were assessed by standard plaque assay. Excised corneas were stained for CD45 and beta-III tubulin. Corneal flow cytometry was performed to assess changes in leukocyte subpopulations. Corneal sensation was measured using a Cochet-Bonnet esthesiometer. Naïve, sham-infected (post scarification), and McKrae-infected C57BL/6 corneas served as two negative and positive controls, respectively. Compared to Ld infected mice, Hd HSV-1 KOS-63 demonstrated higher incidence of corneal opacity (1.5 ×) and neovascularization (2.6 × ; p < 0.05). At 7 dpi Hd infected mice showed more severe corneal opacity (2.23 vs. 0.87; p = 0.0003), neovascularization (6.00 vs. 0.75; p < 0.0001), and blepharitis (3.11 vs. 2.06; p = 0.001) compared to the Ld group. At 3 dpi epitheliopathy was significantly larger in the Hd group (23.59% vs. 3.44%; p = 0.001). Similarly, corneal opacity was significantly higher in Hd McKrae-infected corneas as compared with Ld McKrae-infected corneas at 3 and 5 dpi. No significant corneal opacity, neovascularization, blepharitis, and epitheliopathy were observed in naïve or sham-infected mice. Higher viral titers were detected in corneas (1 and 3 dpi) and trigeminal ganglia (TG) (3 and 5 dpi) in Hd versus Ld KOS-63 groups (p < 0.05). Leukocyte density showed a gradual increase over time from 1 to 7 dpi in both KOS-63 and McKrae-infected corneas. Corneal flow cytometric analysis (3 dpi) demonstrated a higher percentage of Gr-1 + (71.6 vs. 26.3) and CD11b + (90.6 vs. 41.1) cells in Hd versus Ld KOS-63 groups. Corneal nerve density significantly decreased in both Hd KOS-63 and Hd McKrae infected corneas in comparison with naïve and sham-infected corneas. At 3 dpi corneal nerve density was lower in the Hd versus Ld KOS-63 groups (16.79 vs. 57.41 mm/mm2; p = 0.004). Corneal sensation decreased accordingly at 5 and 7 dpi in both Ld and Hd KOS-63-infected mice. Corneal inoculation with HSV-1 KOS-63 strain shows acute keratitis and nerve degeneration in a dose-dependent fashion, demonstrating virulence of this strain.